The Memory of Land in Cherríe Moraga’s Heroes and Saints - Havranová, Katarína (Hungarian Journal of English and American Studies, 2020)
Chicana playwright Cherríe Moraga attributes healing power to memory, which has an important geographical dimension in her play Heroes and Saints (1994). The play dramatizes the suffering of a community of Mexican Americans in California, whose women and children are affected by toxic poisoning as a consequence of agriculture’s overt reliance on pesticides. Whereas critical discussions have dealt extensively with the representation of the body in the play, this study argues for the recognition that the land and the particular places the individual characters inhabit have a decisive impact on the formation of the body. The memory of the land—the Mexican homeland of the immigrant people and the lands of a transnational Latino imagination—is a transformative force in the play, which impels the community to recognize the need to stand up for their rights.